An Automated and Process-Portable Generator for Phase-Locked Loop - Wang, Zhongkai; Choi, Minsoo; Chang, Eric; Wright, John; Bae, Wooham; Du, Sijun; Liu, Zhaokai; Narevsky, Nathan; Schmidt, Colin; Biwas, Ayan; Nikolic, Borivoje; Alon, Elad (2021 58th ACM/IEEE Design Automation Conference (DAC), 2021)
We present a bang-bang phase-locked loop (PLL) generator that encapsulates design methodologies for its circuit blocks and the complete PLL system. The generator is fully automated and parameterized, producing the layout and schematic based on process characterization and top-level specifications. Three 14GHz PLLs are instantiated in TSMC 16nm, GF 14nm and Intel 22nm technologies, demonstrating the process portability. The rapid generation time of less than four days enables fast PLL design and technology porting. The PLL design fabricated in TSMC 16nm shows RMS jitter of 565.4fs and power of 6.64mW from a 0.9V supply.